The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/acps.12839
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental origins of abnormal cortical morphology in dissociative identity disorder

Abstract: Objective To examine the two constitutes of cortical volume (CV), that is, cortical thickness (CT) and surface area (SA), in individuals with dissociative identity disorder (DID) with the view of gaining important novel insights into the underlying neurobiological mechanisms mediating DID. Methods This study included 32 female patients with DID and 43 matched healthy controls. Between‐group differences in CV, thickness, and SA, the degree of spatial overlap between differences in CT and SA, and their relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 59 publications
4
33
0
3
Order By: Relevance
“…28 Traumatic experiences were measured with the Traumatic Experience Checklist. 29 As expected and previously reported, 19 psychoform and somatoform dissociative symptoms and depersonalisation scores were significantly higher in the DID group as compared with healthy controls (all P-values <0.001). Individuals with DID also scored significantly higher compared with the controls for traumatic experiences (all P-values <0.001) on all five adverse life event categories, namely emotional neglect, emotional abuse, physical abuse, sexual abuse and sexual harassment (see Supplementary Table 1).…”
Section: Participantssupporting
confidence: 86%
See 3 more Smart Citations
“…28 Traumatic experiences were measured with the Traumatic Experience Checklist. 29 As expected and previously reported, 19 psychoform and somatoform dissociative symptoms and depersonalisation scores were significantly higher in the DID group as compared with healthy controls (all P-values <0.001). Individuals with DID also scored significantly higher compared with the controls for traumatic experiences (all P-values <0.001) on all five adverse life event categories, namely emotional neglect, emotional abuse, physical abuse, sexual abuse and sexual harassment (see Supplementary Table 1).…”
Section: Participantssupporting
confidence: 86%
“…The DID and healthy control group were carefully matched for demographics including age, gender (all female), years of education and Western European ancestry. As previously shown, 19 we did not find any significant differences between patients and healthy controls with respect to age or education (see Supplementary Table 1 available at ). As part of the inclusion criteria, it was confirmed that all healthy controls were free of medication and psychiatric disorders.…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…Studies of patients with DID and comorbid PTSD reveal decreased temporal lobe cortical volume and cortical surface area compared to healthy controls. 115,116 For example, an MRI study of 15 female patients with DID revealed a 19.2% decrease in hippocampal volume and a 31.6% decrease in amygdala volume compared to controls. 117 Case reports, along with small SPECT studies of patients with DID, have demonstrated consistently that compared to healthy controls and DID simulators, patients with DID show increased perfusion in the left temporal lobe and that temporal perfusion increases while in a dissociated self-state.…”
Section: Resultsmentioning
confidence: 99%